Books and journals reviews - Mora García, José Pascual; Rojas, Reinaldo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
In this section you will find reviews of books and journals related to the history of the Latin American education.